Visualized Real‐Time and Spatial High‐Temperature Sensing in Air‐Stable Organic Films. Issue 10 (11th August 2020) - Yao, Feng; Kong, Mengfei; Yan, Bohan; Li, Ying; Guo, Qingyi; Li, Jiewei; Wang, Shuangqing; Guo, Xudong; Hu, Rui; Qian, Yan; Fan, Quli; Yang, Guoqiang
Abstract: Large‐area thin‐film thermometers for high‐temperature and wide‐range gradient thermosensing and thermomapping are difficult to realize, although they are crucial for scientific and industrial applications. Most luminophores encounter significant emission quenching at heating, and among them, inorganic metal‐based materials have difficulty forming uniform and large‐area‐compliant films. Herein, a series of heat‐resistant blue luminophores based on carbazolyl–pyrene‐substituted triarylphosphine oxides is developed. At a high temperature of 260 °C, their films still maintain high brightness (up to 79% of the original luminous intensity at –196 °C) due to the thermo‐populating of the bright high‐lying excited states. By hybridizing with a thermosensitive yellow chromophore presenting both excited state intramolecular proton transfer and J‐aggregation characteristics, fast‐responsive ratiometric film thermometers for air‐stable sensitive and spatial measurements in wide and high‐temperature range are realized. A wide sensitive thermo‐detection range of around 50–225 °C above room temperature is achieved with a relative sensitivity ( S r ) higher than 1% K −1 . The maximum S r reaches 2.14% K −1 at 168 °C. Moreover, the films exhibit fast‐responsive (50 ms detectable) and large‐area (4 × 4 cm 2 ) naked‐eye thermomapping capabilities, comparable to the infrared thermal imaging results. Double‐proof data encryption applying reversible emission thermo‐tuning is also demonstrated. Abstract : Air‐stable, real‐time (50 ms detectable), and large‐area (4 × 4 cm 2 ) naked‐eye‐sensitive thermosensing and thermomapping in a wide and high‐temperature range is realized using organic ratiometric films. The relative sensitivity is higher than 1% K −1 in a wide higher‐temperature range of 66–225 °C, with the maximum reaching 2.14% K −1 at 168 °C. Temperature‐controlled double‐proof data encryption is also demonstrated.